PENGEMBANGAN LKPD BERBASIS INKUIRI TERBIMBING PADA MATERI PROSES PENGATURAN PADA TUMBUHAN KELAS XI UNTUK MELATIHKAN KETERAMPILAN BERIPIKIR KRITIS - Vianita Nur Handayani; Bashri, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
regulation processes in Grade XI that are valid, practical, and effective for training critical thinking skills. The research adopted the 4D development model (Define, Design, Develop, Disseminate), implemented up to the Develop phase. Limited trials were conducted with 36 Grade XI students at MAN Surabaya. Instruments included validation sheets, implementation observation sheets, student response questionnaires, and pretest-posttest items based on Facione's critical thinking indicators. Results showed the LKPD was valid (average 95.68%), highly practical (100% implementation rate and 99.75% positive student responses), and effective, with an average group worksheet score of 89 (all groups above the minimum passing grade) and an N-Gain of 0.67 (moderate category) for critical thinking skills improvement. Self-regulation obtained the highest N-Gain (0.78) and evaluation the lowest (0.55). Therefore, the developed guided inquiry-based LKPD is suitable for use as a biology learning medium in Grade XI. Keywords: student worksheet, guided inquiry, critical thinking, plant regulation, high school biology.